Experimental Aqueous Alteration of Cortical Bone Microarchitecture Analyzed by Quantitative Micro-Computed Tomography - Kral, Anna G.; Ziegler, Alexander; Tütken, Thomas; Geisler, Thorsten (Frontiers in Earth Science, 2021)
Bones are one of the most common vertebrate fossil remains and are widely used as proxy archives in palaeontology and archaeology. Previous histological analyses have shown that bone microarchitecture is mostly well-preserved in fossil remains, but partially or even entirely lost in most archaeological specimens. As a consequence, processes occurring during early diagenesis are pivotal for the preservation of bones and a better understanding of these processes would be required to assess the significance of information stored in fossilised bones. Although much of the changes occur at the nanometer level, determining the resistance of bone microarchitecture to diagenetic alteration on a microscopic scale constitutes a prerequisite for more detailed studies. Here, results from the first comparative in vitro taphonomy study of cortical bone simulating conditions potentially encountered in early diagenetic settings are presented. In order to accelerate anticipated early diagenetic changes and to facilitate their study in a practical framework, cortical bone samples were exposed to aqueous solutions with temperature, time, and composition of the experimental solutions as controlled parameters. Before and after the experiments, all samples were characterised quantitatively using micro-computed tomography to document structural changes. The results show that the overall change in cortical porosity predominantly occurred in canals with diameters ≤9 µm (∆ Ct.Po = ±30 %). Furthermore, the data also show that the solution composition had a stronger impact on changes observed than either temperature or time. It was also found that samples from the two experimental series with a freshwater-like solution composition showed a characteristic reaction rim. However, it remains unclear at present if the observed changes have an impact on reactions occurring at the nanometer level. Nonetheless, the results clearly demonstrate that on a microscopic scale down to 3 µm, bone microarchitecture is largely resistant to aqueous alteration, even under very different physicochemical conditions. In addition, the data illustrate the complexity of the interaction of different diagenetic factors. The results presented here provide a solid base for further investigations on reaction and transport mechanisms occurring during the early diagenesis of fossil bones.